Implementation of Techno Pedagogy Approch-Based Multiliteration Models in Improving the Skills of Writing the Narration of Elementary School Students - Sulastri, Sulastri; Hartati, N. Tatat; Herawati, Ignasia Anggi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Writing skills are a complex language activity. Writing activities are a combination of skills to use words and sentences, convey ideas and ideas coherently in a writing.ills are a complex language activity. Writing activities are a combination of skills to use words and sentences, convey ideas and ideas coherently in a writing. In the learning process it is necessary to do innovative fun ways so that students' creativity in writing can develop. This research is motivated by a problem that is the lack of narrative writing skills. This study aims to develop narrative writing skills with a multiliteration model based on the techno pedagogy approach. The method used in this research is the literature study method. The results of this study are: (1) The process of using a multiliteration model based on the techno pedagogy approach can improve narrative writing skills; (2) The syntax of applying a multiliteration model based on the techno pedagogy approach; 3) Strengths and weaknesses of the techno pedagogy approach based on multiliteration models